A mutual regulatory loop between miR-155 and SOCS1 influences renal inflammation and diabetic kidney disease - Ignacio Prieto; María Kavanagh; Luna Jimenez-Castilla; Marisa Pardines; Iolanda Lazaro; Isabel Herrero del Real; Monica Flores-Muñoz; Jesus Egido; Oscar Lopez-Franco; Carmen Gomez-Guerrero (Elsevier, 2023)
Diabetic kidney disease (DKD) is a common microvascular complication of diabetes, a global health issue. Hyperglycemia, in concert with cytokines, activates the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway to induce inflammation and oxidative stress contributing to renal damage. There is evidence of microRNA-155 (miR-155) involvement in diabetes complications, but the underlying mechanisms are unclear. In this study, gain- and loss-of-function experiments were conducted to investigate the interplay between miR-155-5p and suppressor of cytokine signaling 1 (SOCS1) in the regulation of the JAK/STAT pathway during renal inflammation and DKD. In experimental models of mesangial injury and diabetes, miR-155-5p expression correlated inversely with SOCS1 and positively with albuminuria and expression levels of cytokines and prooxidant genes. In renal cells, miR-155-5p mimic downregulated SOCS1 and promoted STAT1/3 activation, cytokine expression, and cell proliferation and migration. Conversely, both miR-155-5p antagonism and SOCS1 overexpression protected cells from inflammation and hyperglycemia damage. In vivo, SOCS1 gene delivery decreased miR-155-5p and kidney injury in diabetic mice. Moreover, therapeutic inhibition of miR-155-5p suppressed STAT1/3 activation and alleviated albuminuria, mesangial damage, and renal expression of inflammatory and fibrotic genes. In conclusion, modulation of the miR-155/SOCS1 axis protects kidneys against diabetic damage, thus highlighting its potential as therapeutic target for DKD.